INNOVATIVE EDUCATIONAL ENVIRONMENT AS A SPACE FOR DEVELOPING LEADERSHIP QUALITIES IN FUTURE MANAGERS AND ENTREPRENEURS - Sergiіenko, Tetiana (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
The article explores the concept of an innovative educational environment as a key factor in preparing competitive specialists in the fields of management and entrepreneurship. It analyzes modern approaches to the development of leadership qualities in higher education students, particularly in the context of the integration of education, science, and business. The role of digital technologies, interdisciplinary learning, gamification, mentorship, and project-based activities in developing leadership competencies is discussed. The importance of fostering innovative thinking, strategic vision, emotional intelligence, and communication flexibility as components of effective leadership is emphasized. Special attention is given to examples of the implementation of innovative educational practices in higher education institutions that ensure close interaction with the real business environment. The author justifies the need for the transformation of traditional educational models in line with the needs of the 21st-century labor market to successfully prepare the new generation of managers and entrepreneurs.